Investigating the role of morningness/eveningness in physical activity engagement. Issue 1 (31st December 2022) - Nicholson, Lauren; Mullan, Barbara; Liddelow, Caitlin
ABSTRACT: Objective: Despite being aware of the positive health-related outcomes of physical activity, many people remain inactive. The aim of this study is to apply a combination of constructs from the health action process approach and self-determination theory, as well as habit and morningness/eveningness, to predict physical activity engagement. Methods: A prospective design was used to collect data from 136 participants (16–64 years old), at two-time points, one week apart. The sample consisted of 99 women, 36 men and 1 individual who identified as non-binary. Participants preferred time-of-day was measured using the Morningness-Eveningness Stability Scale (MESSi), while physical activity engagement was measured using the International Physical Activity Questionnaire (short-version). Two hierarchical, multiple regressions were conducted, to predict motivation to engage and to directly predict physical activity engagement. Furthermore, a mediation analysis was conducted to determine the effect of planning on physical activity engagement. Results: Results showed that younger individuals and those with greater self-efficacy were more motivated to engage while planning directly predicted physical activity engagement. However, morningness/eveningness did not significantly predict engagement. Additionally, planning was found to mediate the motivation-engagement relationship. Conclusion: This study demonstrates how planning influences individuals' physical activity engagement, as well as the role self-efficacy and age play in their motivation to engage. Even though morningness/eveningness was not an important predictor, behaviour change techniques related to action planning and the use of multi-component approaches to behaviour change, could be used in interventions focused on increasing individuals' physical activity engagement.